2015
DOI: 10.3389/fncel.2015.00369
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic regulation of synaptic plasticity in the mouse primary visual cortex: analysis of matrix metalloproteinase 9 deficient mice

Abstract: The extracellular matrix (ECM) is known to play important roles in regulating neuronal recovery from injury. The ECM can also impact physiological synaptic plasticity, although this process is less well understood. To understand the impact of the ECM on synaptic function and remodeling in vivo, we examined ECM composition and proteolysis in a well-established model of experience-dependent plasticity in the visual cortex. We describe a rapid change in ECM protein composition during Ocular Dominance Plasticity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 108 publications
(184 reference statements)
5
27
0
Order By: Relevance
“…In WT adults, LRx promoted a significant enhancement of non-deprived eye VEP following MD (between subjects repeated measures ANOVA, F (df,1,8) =6.33, p=0.026, MD n=12, MD+LRx n=8). However, we did not observe an increase in the strength of the non-deprived input in Mmp9 −/− mice, consistent with previous reports ( Spolidoro et al, 2012 ; Kelly et al, 2015 ; Pielecka-Fortuna et al, 2015 ) and observed no reactivation of the response to MD after LRx (between subjects repeated measures ANOVA F (df,1,5) =0.633, p=0.890; MD n=6, MD+LRx n=5; Figure 6A ). During the critical period for ocular dominance plasticity, MD induces a significant decrease in the density of dendritic spines on pyramidal neurons in deprived V1b (contralateral to the occlusion), but this plasticity is lost with age ( Mataga et al, 2004 ).…”
Section: Resultssupporting
confidence: 93%
“…In WT adults, LRx promoted a significant enhancement of non-deprived eye VEP following MD (between subjects repeated measures ANOVA, F (df,1,8) =6.33, p=0.026, MD n=12, MD+LRx n=8). However, we did not observe an increase in the strength of the non-deprived input in Mmp9 −/− mice, consistent with previous reports ( Spolidoro et al, 2012 ; Kelly et al, 2015 ; Pielecka-Fortuna et al, 2015 ) and observed no reactivation of the response to MD after LRx (between subjects repeated measures ANOVA F (df,1,5) =0.633, p=0.890; MD n=6, MD+LRx n=5; Figure 6A ). During the critical period for ocular dominance plasticity, MD induces a significant decrease in the density of dendritic spines on pyramidal neurons in deprived V1b (contralateral to the occlusion), but this plasticity is lost with age ( Mataga et al, 2004 ).…”
Section: Resultssupporting
confidence: 93%
“…Finally, the enrichment of DEGs that contribute to the ECM in the 5-week RTT samples is interesting in view of the contribution made by microglia, albeit modest compared with astrocytes and neurons, to ECM homeostasis [7781]. Considering the importance of the ECM in maintaining synaptic function, the altered expression of ECM components and regulators in the pre-phenotypic phase could play some role in the synaptic dysfunction that ultimately leads to clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that especially MMP-9 and MMP-3 play a pivotal role in these processes [ 30 36 ]. More recently, it has been shown that in the cortex both MMPs are involved in learning and in the plasticity processes [ 36 39 ]. In particular, Kaliszewska et al [ 38 ] have shown that MMP-9 knockout resulted in a decreased plasticity in layer IV and II/III in barrel cortex of adult mice.…”
Section: Introductionmentioning
confidence: 99%